Environmental Education in an Islamic Perspective: An In-Depth Study Based on Sufism - Lutfauziah, Asmaul; Aris Handriyan; Djoko Hartono; Fifi Khoirul Fitriyah (Universitas Nahdlatul Ulama Surabaya, 2022)
Environmental education has not been studied in Islamic boarding schools, so students do not maintain cleanliness and do not understand the meaning of environmental education. In contrast, environmental education is a teaching of Islam. Recently, much research that combines environmental education with Sufism teachings is still not widely done. This study aims to describe environmental education from an Islamic point of view, especially from a Sufism perspective. Qualitative research with a systematic literature review was employed in this study. Three steps consisted of planning, conducting, and reporting were geared to collect the data. The results indicated that 1) Sufism taught environmental ethics. As a result, students had more noble character because Sufism covered various aspects of human activities; 2) The environment functioned as a verse (a sign of God's greatness), as material for reflection (tafakur) to take lessons and media to fulfill human needs, as a manifestation of God's form, and as a means for God to introduce Himself to humans; 3) Allah SWT created his creation for two purposes. Those are a servant of Allah SWT and as caliphs on earth, so the people always seek knowledge to recognize Allah (ma'rifatullah); and 4) the scope of environmental education in the perspective of Sufism included the physical realm, the spiritual realm, the realm of sentences, and the nature of God's substance. Sufism is needed to establish human morals toward the environment so that humans sincerely preserve and do not damage the environment. This is based on the nature of compassion for the environment as a manifestation of the nature of the mercy of God's womb. The ultimate goal is that humans reach the highest degree, which is knowing God (ma'rifatullah). Environmental education belum dipelajari di pesantren sehingga santri kurang menjaga kebersihan dan belum memahami makna environmental education. Padahal environmental education merupakan ajaran agama Islam. Pada saat ini, penelitian yang mengkombinasi environmental education dengan ajaran tasawuf masih belum banyak dilakukan. Penelitian ini bertujuan untuk mendeskripsikan pendidikan lingkungan dari sudut pandang Islam khususnya dari perspektif tasawuf. Penelitian ini merupakan penelitian kualitatif with systemtic literature review. The procedures consist of three steps. They are planning, conducting, and reporting. Hasil penelitian ini menunjukkan bahwa 1) ajaran tasawuf mengajarkan etika lingkungan agar manusia semakin berakhlak mulia karena tasawuf mencakup berbagai aspek kegiatan manusia, 2) lingkungan berfungsi sebagai ayat (tanda kebesaran Allah), sebagai bahan renungan (tafakur) guna mengambil hikmah dan pelajaran, media untuk pemenuhan kebutuhan manusia, sebagai manifestasi dari wujud Tuhan serta sebagai sarana Tuhan mengenalkan diri-Nya pada manusia, 3) manusia diciptakan oleh Allah SWT pada dasarnya memiliki dua peran yaitu sebagai hamba Allah SWT dan sebagai khalifah di muka bumi agar manusia mencari ilmu untuk mengenali Allah (ma’rifatullah), dan 4) ruang lingkup environmental education dalam perspektif tasawuf meliputi a) alam fisik, b) alam ruhani, c) alam kalimat, dan d) alam zat Allah. Tasawuf diperlukan dalam pembentukan akhlak manusia terhadap lingkungan sehingga manusia secara ikhlas menjaga kelestarian lingkungan dan agar tidak berbuat kerusakan lingkungan. Hal ini didasari karena sifat kasih sayang kepada lingkungan sebagai manifestasi sifat rahman rahim Allah. Tujuan akhirnya yaitu manusia mencapai derajat tertinggi yaitu mengenal Tuhan (ma’rifatullah).